Development of miRNA-mimic nanoparticles for the treatment of brain tumours - Anithiya Ramamoorthi Gopalram, Shubaash (2017)
Glioblastoma are aggressive brain tumours with a median survival of 15 months even with the best currently available treatment options. microRNAs (miRNA) are ~23 nucleotide natural silencing RNAs that have great potentials to improve cancer treatment outcomes. Lack of a safe, stable and efficient delivery system has, however, hindered the use of miRNAs in clinical applications. The aim is therefore to develop a miRNA delivery system adapted to glioblastoma using linear chain cationic polyamidoamine (PAA) polymers. The first part involved the development of luciferase assay that combined the measurement of gene-knockdown efficiency and cytotoxicity of miRNA nanoparticles. The simple two-step procedure was more effective and sensitive compared to the conventional protein-based normalization method. The second part was focused on the development of miRNA nanoparticles. In the initial phase, conditions required for maximum miRNA-polymer binding was achieved, however, the newly developed miRNA-PAA-nanoparticles did not produce significant functional gene-knockdown after cell treatment. The second stage was focused on the optimization of nanoparticle formulation as a function of stability in physiological ionic concentration. Stable PAA-nanoparticles displaying moderate cellular uptake and gene-knockdown were obtained. The final stage of development was focused on PAA-nanoparticle tagging with biotin, which improved their cellular uptake. This work developed simple and informative luciferase assay; the stability of miRNA-PAA-nanoparticles was improved by thiol-crosslinking and the cellular uptake was enhanced by a simple but smart method of ligand tagging. Further optimizations are needed to increase the functional performance of these potential and clinically relevant thiol-stabilized RNAi vectors.